2015
DOI: 10.1002/14651858.cd001450.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and umbilical Doppler ultrasound in normal pregnancy

Abstract: Cochrane Database of Systematic Reviews Analysis 2.3. Comparison 2 Single Doppler ultrasound assessment versus no Doppler ultrasound, Outcome 3 Neonatal death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 57 publications
3
114
1
5
Order By: Relevance
“…These LMIC results confirm Cochrane reviews of the impact of routine use of US during ANC in HIC. [7][8][9][10] It is important to emphasise what we did and did not study. We studied the provision of two routine basic US examinations during ANC with the earliest examinations at 16 weeks coupled with referrals to a hospital for certain obstetric conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These LMIC results confirm Cochrane reviews of the impact of routine use of US during ANC in HIC. [7][8][9][10] It is important to emphasise what we did and did not study. We studied the provision of two routine basic US examinations during ANC with the earliest examinations at 16 weeks coupled with referrals to a hospital for certain obstetric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One Cochrane review concluded that introducing routine US in resource-constrained healthcare settings could place a large burden on available resources, detracting from other more beneficial services. 10 The introduction of various interventions without proof of efficacy in achieving an important clinical outcome is not uncommon either in obstetrics or in medicine in general. 31 Adopting interventions used in high-income countries in resource-limited areas without proof of efficacy in those locations also occurs frequently.…”
Section: Interpretation [In the Light Of Other Evidence]mentioning
confidence: 99%
See 1 more Smart Citation
“…SA studies have demonstrated that it can be used at primary healthcare level by nurses and midwives. [30,31] Although a recent meta-analysis in high-income countries found that Doppler or Umbiflow use in low-risk pregnancies was not effective in reducing perinatal mortality, [32] there may be a potential benefit of Umbiflow use in lowrisk populations in LMICs to refer women to higher-level care. [33] Another interesting finding in the present study was the increased stillbirth risk seen in LGA pregnancies between 36 Fig.…”
Section: Researchmentioning
confidence: 99%
“…Although several studies indicate no harmful effects [1][2][3] , some studies report potential bioeffects on human fetuses 4,5…”
Section: Introductionmentioning
confidence: 99%